Efficacy and tolerability of the fixed lercanidipine-enalapril combination in the treatment of patients with essential hypertension - Rump, Christian L. (Arzneimittelforschung, 2010)
The purpose of this first prospective observational cohort study after launch was to document the efficacy and tolerability of therapy with the fixed combination of lercanidipine HC1 (CAS 132866-11-6), a third-generation calcium antagonist, and the angiotensin converting enzyme (ACE) inhibitor enalapril maleate (CAS 76095-16-4) in patients with essential hypertension in daily practice. Both parts of the observational study were conducted with the fixed combination of enalapril maleate 10 respectively 20 mg and lercanidipine HC1 10 mg, one part with Zaneril® and the other with Zanipress®. The fixed combination is marketed under these product names in Germany.The data of 8,440 patients with a mean age of 62 years and a mean body mass index (BMI) of 28 kg/m2 were evaluated. 84% of the patients had already received pre-treatment for essential hypertension. 26% of all the patients were known to have had hypertension for at least 10 years. Around 70% had further concomitant diseases.The mean blood pressure before the beginning of the study was 162.5/94.5 mmHg, the mean reduction after around three months was 28.4/13.5 mmHg. Just under 80% of the patients reached the desired target blood pressure after the observation period.The global assessment of the physicians shows that the efficacy of the drugs was “very good” to “good” for 94% of the patients. Global tolerability was assessed as “very good” and “good” for 97% of the patients. Compliance was stated as “very good” and “good” for 97% of the patients. Adverse drug reactions were documented for 2% of all patients.
Keywords: Antihypertensive fixed combination; Enalapril; Essential hypertension; Lercanidipine; Zaneril®; Zanipress®